Efectividad del proceso de selección por competencias para docentes de un colegio privado - Regalado Tamayo, Jennifer (2017)
The main objective of this research is to study the effectiveness of the competency based recruitment process for teachers of a private school in the city of Quito. First, it analyzes the institution's background regarding recruitment processes to understand the actors, tools, methodology and used criteria. Assess the performance evaluation of 20 teachers who have been selected under the competency-based model. Hence, identify how effective the recruitment has been. In addition, a tool is proposed to create management indicators that allow the institution to measure and evaluate the effectiveness of the process. Thus, reflecting the consequences of the actions carried out and directing to continuous monitoring, focusing on those points of improvement and boosting the strengths of the process. The Principal, who is in charge of teaching staff recruitment and its performance evaluation will be participating actively throughout the research Keywords: competency-based recruitment, performance evaluation, management indicators